The Dynamics of Inter-firm Cooperation within Global Business (Department of International Relations, Universitas Brawijaya, 2023)
Inter-firm cooperation has been a long-established practice within the modern world of business. This paper, therefore, aims at examining this fact by tracking the dynamics of inter-firm cooperation in the past three centuries. The finding suggests that the purpose of strategic alliances among industries has altered after 1945. Industrial alliances prior to 1945 were motivated by increasing profits through market sharing, thus they operated like cartels. The cooperative capitalistic system was in question, nevertheless, when the idea of liberalism flourished after 1945. Major power such as the United States and its allies urged countries began to establish anti abuse of cooperation regulations and firms to start adopting competitive models of business. The inter-firm cooperation, in fact, did not diminish. Since the beginning of 1980s, there has been a trend for the re-emergence of the cooperative model of business between international firms. Unlike in the pre-World War II era, strategic alliance today has been established particularly within industries where innovation and technological development is crucial. Some factors have been identified as to shape this new development, including the governments’ permission, an increasing cost for research and development, the emergence new competitors across the globe, and the need for developing expertise.